The Influence of Problem Based Learning Models and Metacognition Knowledge on Students Mathematics Learning Outcomes - Purba, R. Ellen Della; lsanosi, Mohammed najy E; Kohlhoff, Pauline (Program Magister Teknologi Pendidikan Universitas Jambi, 2022)
The aim of this research is to explore and identify the influence of using the Problem Based Learning (PBL) model on the mathematics learning outcomes of class VII students at Public Middle School 1 Tanjung Jabung Timur, as well as to understand the relationship between students' metacognitive knowledge and their learning outcomes in the context of using the PBL model. In this study, the research design followed a 2x2 factorial design with a pretest and posttest. The sampling technique in this research used simple random sampling. The experiment consisted of 4 meetings in a series of activities, namely the first was pre-learning preparation and group division and determining group leaders. The instruments in this research used a metacognitive knowledge questionnaire and learning outcomes tests. Analysis of this research data uses a pretest average similarity test (one way ANOVA). Based on research on the use of the PBL model in class VII students at Public Middle School 1 Tanjung Jabung Timur, it can be concluded that the PBL model has a positive effect on students' mathematics learning outcomes, with a higher level of achievement compared to the conventional approach. In addition, metacognitive knowledge also influences mathematics learning outcomes, where students with high metacognitive knowledge show statistically significant differences compared to students who have low metacognitive knowledge.